Islamic Custom of Letter and Seal in Sarakata Manuscript “Surat-Surat dari Aceh” - Rakhadiyanti, Mustika Ayu; Limbong, Priscila Fitriasih (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
This paper presents a study on Sarakata manuscripts from the collection of the National Library of the Republic of Indonesia. The Sarakata analyzed in this research is entitled "Surat-Surat dari Aceh" with the code ML 447 written in the 19th century Jawi script. This Sarakata consists of nine letters, four of which are analyzed in this study, namely Sarakata 3, 5, 6, and 7. These Sarakatas are selected due to their historical, economic, political, social, and Islamic law aspects. The text structure is examined using 'guidance of correspondence' in Kitab Tarasul. It is found that compared to Tarasul, SSA sarakata has five elements, one of which is not contained in Kitab Tarasul, namely the pledge. The different correspondence formats are due to the fact that Aceh has its Islamic proprietary custom. Another segment under analysis was the Sarakata stamp (sikureueng seal) which the Aceh sultans used in establishing important royal letters. This seal consists of one or nine circles with different designs and decorations depicting each king's arts and specific objectives. The present study examines this usage by employing the semiosis process by Pierce. The study results indicate that the sikureueng seal, adorned with natural and geometric shapes, represented meanings such as a yearning of growth, peace, welfare, life, and longevity.